2018
DOI: 10.1111/1753-0407.12620
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of metallothionein: Clinical implications for patients with diabetes mellitus

Abstract: Reactive oxygen and nitrogen species (ROS and RNS, respectively) are byproducts of cellular physiological processes of the metabolism of intermediary nutrients. Although physiological defense mechanisms readily convert these species into water or urea, an improper balance between their production and removal leads to oxidative stress (OS), which is harmful to cellular components. This OS may result in uncontrolled growth or, ultimately, cell death. In addition, ROS and RNS are closely related to the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 168 publications
(602 reference statements)
0
17
0
Order By: Relevance
“…Metallothionein (MT) is a cysteine-rich protein that binds metals such as zinc (Zn). As a potent antioxidant, MT is highly efficient in scavenging or quenching various reactive oxygen species (ROS) that play critical roles in the onset and development of diabetes and diabetic complications (7). The importance of MT in diabetic complications has been demonstrated in previous studies in MT transgenic mice.…”
mentioning
confidence: 99%
“…Metallothionein (MT) is a cysteine-rich protein that binds metals such as zinc (Zn). As a potent antioxidant, MT is highly efficient in scavenging or quenching various reactive oxygen species (ROS) that play critical roles in the onset and development of diabetes and diabetic complications (7). The importance of MT in diabetic complications has been demonstrated in previous studies in MT transgenic mice.…”
mentioning
confidence: 99%
“…Metallothionein can be induced by a variety of conditions including high glucose (17,18), and plays a crucial role in mediating anti-apoptosis and anti-inflammation. By modulating stress- induced signaling pathways of Wnt, NF-kB, and PI3K, Metallothionein can alleviate diabetes and diabetic complications (19). Fasting resulted in a significant increase in metallothionein 1 gene expressions in retroperitoneal, epididymal, and inguinal white adipose tissue of rats, and this effect was reversed by refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, the overexpression of MT in streptozotocin-induced diabetic mice caused lower levels of β-cell DNA damage and oxidative stress. While this classical view of MT as an antioxidant has been confirmed, a review by Park et al (2018) suggests new mechanisms of action for MT [ 34 ].…”
Section: Zinc Transporters: Glucose Homeostasis Insulin Resistance and Immunitymentioning
confidence: 99%
“…First, the authors proposed that MT may counteract oxidative stress by reversing mitochondrial dysfunction, which is the main source of ROS. Mitochondrial dysfunction is a primary contributor to many diabetic issues including β-cell impairment, IR, endothelial dysfunction, and vascular damage [ 6 , 34 ]. The precise mechanism surrounding MT’s effects on the respiratory chain are unclear, but studies have demonstrated that MT protects against mitochondrial superoxide (O 2 •− ) over-production and exerts myocardial anti-apoptotic effects induced by mitochondrial dysfunction [ 34 , 35 , 36 ].…”
Section: Zinc Transporters: Glucose Homeostasis Insulin Resistance and Immunitymentioning
confidence: 99%
See 1 more Smart Citation